(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In paper, is given overview of sorbents with ferromagnetic particles. The series of newly designed composite sorbents SOMSOR, are described. Described experiment of oil spill collection from water surface, which comprises of sorbent spreading and collection. Oil sorption by capillary forces, is discussed. Concluded that use of ferromagnetic sorbents a promising direction in the field of water purification from light oil products since it allows expanding the scope of the used powder sorbents, to use the high-mechanized methods of collecting by means of magnetic and electromagnetic devices.